Comparative Assessment of Emotional Intelligence of Prospective and Working Secondary Teachers of Delhi- - Agarwal, Nidhi; Gupta, Ruchika; Chandra, Geetanjali (International Journal of Psychosocial Rehabilitation, 2020)
Emotional intelligence can predict students’ academic performance and employees’ workplace professional performance. The present paper is a research-based study in secondary schools in Delhi and NCR to explore the emotional intelligence quotient in service teachers and prospective secondary teachers doing internships with effective teaching and learning. With the mushrooming of educational institutes in India, it is very important that the teachers today have a high EI to ensure better transfer of knowledge. The study uses data collected from prospective secondary teachers doing their internship and in-service secondary teachers of the NCR region by the normative survey method. The study results have uncovered that there exists a noteworthy distinction in emotional intelligence between prospective and working teachers, which further gets distinguished based on gender. Male teachers areed to be more emotionally clever than the female teachers. The findings of this study may likewise be useful to the specialists of educational organizations.